ANXIOLYTIC EFFECT OF MIDAZOLAM PREMEDICATION ASSESSED BY CLINICAL AND PLATELET AGGREGATION PROFILES - Khan, Ehtesham I.; Kamal, Rehana S.; Ullah, Hameed (Journal of Ayub Medical College Abbottabad, 2010)
Background: It is well documented that surgery is associated with increased anxiety, which has an adverse impact on patient’s outcome. This study was designed to assess the anxiolytic effect of midazolam in pre-anaesthetic medication by using clinical and platelet aggregation profiles. Methods: Sixty ASA I and II female patients aged between 35 and 60 years undergoing elective abdominal hysterectomy were randomly divided into two equal groups. Group I received placebo as pre-medication while group II received 0.15 mg/kg midazolam as pre-medication 1 hour preoperatively. They were monitored for visual analogue scale (VAS) for anxiety, observer’s anxiety criteria, sedation score, blood pressure, heart rate and platelet aggregation profile immediately before and 1 hour after pre-medication. Results: There was statistically significant difference with respect to VAS of anxiety, observer’s anxiety criteria, sedation scores, systolic and diastolic blood pressure (p<0.05). Heart rate was higher in the midazolam group but this was not statistically significant. There was no statistical significant difference in platelet aggregation profile in the two groups. Conclusion: Findings of the study suggest midazolam is a good anxiolytic for pre-medication and its effect on platelet aggregation profile needs to be further evaluated. Keywords: Pre-medication, Widazolam, Anxiolysis, Platelet aggregation